HEALTHY PERCEPTION BASED HEALTH BELIEF MODEL WITH SEEKING BEHAVIOR OF RUBBER FARMERS AT SENTOOL PLANTATION, SUCI VILLAGE, PANTI DISTRICT, JEMBER REGENCY - Retno Purwandari; Alfid Tri Afandi; Nafisatus Shofiyyah; Anisah Ardiana; Dicky Endrian Kurniawan (UNEJ e-Proceeding, 2023)
Background: Perception is a process of giving meaning, interpretation, and sensation that is received by each individual and is strongly influenced by one's internal and external factors. These perceptions have a considerable role to play in behavior change, and efforts should be focused on increasing perceived vulnerabilities, perceived severity, perceived benefits, and perceived barriers. Objective: Analyzing the relationship between perceptions of health based on the Health Belief Model (HBM) and treatment-seeking behavior. Method: This study uses a correlational analytic design with an approach cross-sectional. This study involved 142 respondents obtained randomly. Data were collected using the HBM-based health perception questionnaire and the treatment-seeking behavior questionnaire with data analysis using the rank correlation test spearmen with a 95% confidence interval. Results: Test analysis Spearman rank showed a significant relationship between HBM-based perceptions of health and treatment-seeking behavior and the value of p = <0.001 and r = 0.274. Conclusion: A significant relationship exists between the two variables with weak strength and a positive direction. This shows that the higher the perception of health, the higher the treatment-seeking behavior of rubber farmers. Healthy perception has an important role in maintaining a state of a person who will behave according to his perception. A good perception will be easier to implement behavior to achieve health with appropriate treatment-seeking behavior